2021
DOI: 10.1021/acs.analchem.1c01091
|View full text |Cite
|
Sign up to set email alerts
|

Methanol-Enhanced Liquid Electrode Discharge Microplasma-Induced Vapor Generation of Hg, Cd, and Zn: The Possible Mechanism and Its Application

Abstract: Despite increased interest in microplasma-induced vapor generation (μPIVG) over the past several years, applications in real sample analyses remain limited due to their relatively low vapor generation efficiency and ambiguous mechanism. In this work, a novel method using methanol for significantly enhancing the liquid electrode discharge μPIVG efficiency was developed for the simultaneous and sensitive determination of Hg, Cd, and Zn by atomic fluorescence spectrometry (AFS). It is worth noting that the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…The observed difference in the response between Sb­( iii ) and Sb­( v ) [Sb­( iii ) signal was about 13% higher than that of Sb­(V) at pH = 14, Figure S2] partly supports this hypothesis. It is worth noting that the optimized pH for Sb detection by hydrogen-doped SAGD-OES is quite different with other elements (e.g., Cd, Zn, Ag, Hg, In, Pb, Tl, and Bi), as in other previously reported SAGD-OES studies, of which the optimum pH value was typically under 7. For instance, pH of 3.2 was employed for Cd and Zn detection by SAGD-OES . The results suggest that vapor generation of Sb is more readily affected by H 3 O + ions than other elements.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…The observed difference in the response between Sb­( iii ) and Sb­( v ) [Sb­( iii ) signal was about 13% higher than that of Sb­(V) at pH = 14, Figure S2] partly supports this hypothesis. It is worth noting that the optimized pH for Sb detection by hydrogen-doped SAGD-OES is quite different with other elements (e.g., Cd, Zn, Ag, Hg, In, Pb, Tl, and Bi), as in other previously reported SAGD-OES studies, of which the optimum pH value was typically under 7. For instance, pH of 3.2 was employed for Cd and Zn detection by SAGD-OES . The results suggest that vapor generation of Sb is more readily affected by H 3 O + ions than other elements.…”
Section: Resultsmentioning
confidence: 69%
“…Previous studies reported that SAGD-OES typically suffered from the interference of the coexisting metal ions, especially transition metals (Mn, Ni, and Fe). For instance, Greda et al reported that with the addition of 10 mg L –1 Na, K, Mg, and Ca, the recoveries of Ag, Cd, Hg, In, Pb, and Zn did not exceed 70% . Moreover, the presence of Fe and Mn at 10 mg L –1 depressed the signal of Bi (0.5 mg L –1 ) to less than 20% …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma induced vapour generation (PIVG) has become popular over the last few years, but its application has been mostly limited to synthetic ‘samples’. Pan et al 32 aimed to address this by investigating methanol enhancement for liquid electrode PIVG. The VG manifold was constructed of a PMMA chip into which a tungsten rod (1.6 mm in diameter), and a stainless-steel tube (0.6 mm i.d.…”
Section: Liquids Analysismentioning
confidence: 99%